Appendix 4.4: Excerpt from “A Greater Responsibility for Our Soldiers,” 26 January 1972 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
This excerpt from a recorded exchange between President Marcos and Gen. Guillermo A. Picache, made days after declaring martial law, reinforces dean Raul Pangalangan’s claims to the effect that before Marcos had Javellana v. Executive Secretary , he had Lansang v. Garcia in his arsenal of jurispridence (Marcos 1974, 228–30). Here, Marcos shows that he was willing to submit his very first actions after declaring martial law to legal scrutiny, but only because he was confident that the courts would not challenge him based on the Lansang precedent.